Implementation of the RODE Model to Enhance Students’ Science Numeracy Skills in Higher Education - Degi Alrinda Agustina; Arief Ertha Kusuma; Suciati Suciati; Maulidah Nurislamiyah; Sri Radiatul Hikma; Neni Novitasari (Universitas Lambung Mangkurat, 2026)
This study examines the implementation of the RODE learning model in supporting students' science numeracy skills in a higher education context. The research was conducted in the Primary School Teacher Education department within the Basic Concepts of Astrophysics course, focusing on fluid materials. A qualitative design was employed to describe the planning, implementation, and assessment stages of the RODE model. Data were collected through classroom observations, semi-structured interviews, and documentation, and were analyzed using the interactive model of Miles and Huberman. The findings indicate that, at the planning stage, the lecturer team aligned course learning outcomes with science numeracy indicators and developed instructional materials, including lesson plans, teaching resources, student worksheets, and assessment instruments. During implementation, the RODE syntax was applied through four stages: Read (engagement with learning materials), Outline (concept organization and worksheet-based activities), Discussion (group presentations and interactive dialogue), and Evaluation (reflection and assessment activities). At the assessment stage, students' performance was evaluated through worksheet activities and essay tests designed to reflect science numeracy indicators. The results suggest that the RODE model can be feasibly implemented to support science numeracy by orienting learning processes in higher education. However, the findings are limited to a specific instructional context and do not imply generalizable causal effects. This study contributes by providing a context-specific description of how the RODE model can be integrated with science numeracy practices at the university level.